Assessing pesticide residues occurrence and risks in water systems: A Pan-European and Argentina perspective - Navarro, Irene; De la Torre, Adrián; Sanz, Paloma; Abrantes, Nelson; Campos, Isabel; Alaoui, Abdallah; Christ, Florian; Alcon, Francisco; Contreras, Josefina; Glavan, Matjaž; Pasković, Igor; Polić Pasković, Marija; et al. (Elsevier, 2024)
Freshwater ecosystems face a particularly high risk of biodiversity loss compared to marine and terrestrial systems. The use of pesticides in agricultural fields is recognized as a relevant stressor for freshwater environments, exerting a negative impact worldwide on the overall status and health of the freshwater communities. In the present work, part of the Horizon 2020 funded SPRINT project, the occurrence of 193 pesticide residues was investigated in 64 small water bodies of distinct typology (creeks, streams, channels, ditches, rivers, lakes, ponds and reservoirs), located in regions with high agricultural activity in 10 European countries and in Argentina. Mixtures of pesticide residues were detected in all water bodies (20, median; 8–40 min-max). Total pesticide levels found ranged between 6.89 and 5860 ng/L, highlighting herbicides as the dominant type of pesticides. Glyphosate was the compound with the highest median concentration followed by 2,4-D and MCPA, and in a lower degree by dimethomorph, fluopicolide, prothioconazole and metolachlor(-S). Argentina was the site with the highest total pesticide concentration in water bodies followed by The Netherlands, Portugal and France. One or more pesticides exceeded the threshold values established in the European Water Framework Directive for surface water in 9 out of 11 case study sites (CSS), and the total pesticide concentration surpassed the reference value of 500 ng/L in 8 CSS. Although only 5 % (bifenthrin, dieldrin, fipronil sulfone, permethrin, and terbutryn) of the individual pesticides denoted high risk (RQ > 1), the ratios estimated for pesticide mixtures suggested potential environmental risk in the aquatic compartment studied.